2011
DOI: 10.1007/s00405-011-1811-8
|View full text |Cite
|
Sign up to set email alerts
|

Passive smoking and nasopharyngeal colonization by Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis in daycare children

Abstract: Exposure to tobacco smoke may be associated with higher risk of nasopharyngeal colonization and infection by Streptococcus pneumoniae (SP), Haemophilus influenzae (HI), and Moraxella catarrhalis (MC). This study was done to determine the influence of passive smoking on S. pneumoniae, H. influenzae, and M. catarrhalis colonization rates among children. This is a prospective cross-sectional study. Tertiary referral centers with accredited otorhinolaryngology-head and neck surgery and Microbiology Departments. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
(39 reference statements)
1
9
1
Order By: Relevance
“…However, it was lower than those in Gambia [9], Poland [10], Australia [11], Thailand [12], and higher than those reported from Iran [13] and Korea [14]. The carriage prevalence among adults in our study was 11%, wich is higher than that found in Alaska [15], but lower than that among Australian Aboriginals of the same age [11].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…However, it was lower than those in Gambia [9], Poland [10], Australia [11], Thailand [12], and higher than those reported from Iran [13] and Korea [14]. The carriage prevalence among adults in our study was 11%, wich is higher than that found in Alaska [15], but lower than that among Australian Aboriginals of the same age [11].…”
Section: Discussioncontrasting
confidence: 75%
“…This study provides further evidence that passive smoking is an independent determinant of S. pneumoniae carriage among children [10], [13]. The mechanism by which passive smoking influences the microbial ecology of the upper respiratory tract remains to be elucidated, however.…”
Section: Discussionmentioning
confidence: 59%
“…Principi et al [4] concluded that tobacco smoke exposure of healthy children aged <5 years did not influence pathogen carriage in the upper respiratory tract but a more recent study did show increased S. pneumoniae carriage rates in children exposed to tobacco smoke [33]. By contrast, Bakhshaee et al [34] found a significant difference in carriage rates between children living in smoking families, compared to those in non-smoking families for M. catarrhalis, but not for S. pneumoniae and H. influenzae. In our cohort, passive smoking was a risk factor for increased nasopharyngeal colonization of H. influenzae and this is supported by Kosikowska et al [35] who also found increased colonization of this pathogen in healthy children aged 3-5 years, heavily exposed to tobacco smoke, as well as vulnerability to recurrent respiratory infections.…”
Section: Discussionmentioning
confidence: 97%
“…Comparing the incidence and biotype composition of oropharyngeal carriage of NTHi in mothers affected by obstetric NTHi would be of interest. Oropharyngeal colonisation could provide the source for genital infection, and it is possible that smoking may influence oropharyngeal colonisation, although reports of an association between Hi carriage and smoking are conflicting . An alternative hypothesis for infection source would be sexual acquisition of NTHi infection.…”
Section: Discussionmentioning
confidence: 99%